Character education in Indonesia: How is it internalized and implemented in virtual learning? - Mupid Hidayat; Rama Wijaya Abdul Rozak; Kama Abdul Hakam; Maulia Depriya Kembara; Muhamad Parhan (Jurnal Cakrawala Pendidikan, 2022)
This study investigates teachers' internalization and implementation of character education in schools. This research employed a mixed-method that combines quantitative and qualitative methods. The research data was obtained by distributing questionnaires to 576 elementary school, junior high school, and high school teachers who participated in the e-workshop on developing the competence of character values internalization. The collected data were tabulated and analyzed to know the internalization and implementation of character education carried out by teachers. The results show that teachers implement character education through habituation, integration, and imitation. Teachers have difficulty internalizing and implementing character values when learning is implemented virtually. This problem occurs because teachers are accustomed to having face-to-face interaction with students when implementing character education in schools. This condition has recently become an obstacle in implementing character education because learning is carried out virtually. The research helps implement virtual learning to develop character values.